Principles of Psychological Counseling - Xaitova D.Y.; Sh. Sh. Rustamov (European Science Publishing, 2023)
In today's complex and rapidly developing world, psychological counseling plays a decisive role in a wide variety of areas, from clinical practice to organizational management. However, its importance in the field of scientific research is often overlooked. Within the framework of scientific research, it is aimed at highlighting the theoretical foundations of psychological counseling. Having studied the established theoretical foundations and Real programs, this study seeks to highlight the important role of psychological counseling in ensuring the moral and methodological integrity of research work.
Keywords: psychological consultation, psychological assistance, psychodynamics, approach, behavior, personality, client.